Development-Led or 'Preventive' Archaeology in the Grand Duchy of Luxembourg - Mei Duong (Internet Archaeology, 2021)
The preventive archaeology system in Luxembourg was developed during the 1990s. Archaeological heritage is now managed by the National Archaeological Research Centre/Centre national de recherche archéologique (CNRA), founded in 2011, although there is still no legal framework within which archaeology can be protected. A draft law implementing the principles of the Valletta Convention will provide the structure for the CNRA to assess construction projects and require archaeological investigations. This paper outlines the development of the system, notes the challenges and highlights opportunities to raise public awareness, which are keys to engage the public in local decision making, through the communes.